Peptide Tat(48–60) YVEEL protects against necrotizing enterocolitis through inhibition of toll-like receptor 4-mediated signaling in a phosphatidylinositol 3-kinase/AKT dependent manner - Yan, Xiangyun; Cao, Yan; Chen, Wenjuan; Yu, Qinlei; Chen, Yanjie; Yao, Shuwen; Jiang, Chengyao; Chen, Xiaohui; Han, Shuping (Frontiers in Nutrition, 2022)
Necrotizing enterocolitis (NEC) is a catastrophic disease largely occurring in preterm infants, and toll-like receptor 4 (TLR4) has been implicated in its pathogenesis. The current therapeutic strategies for NEC are, however, far from optimal. In the present study, a whey-derived antioxidative peptide conjugated with a cell-penetrating TAT (Tat (48-60) YVEEL) was prepared to endow it with enhanced cell uptake capability and bioavailability. The protective effect of Tat (48-60) YVEEL on experimental NEC was evaluated both in vitro and in vivo. Inhibition of TLR4-mediated signaling by Tat (48-60) YVEEL was assessed in FHC and IEC-6 enterocytes, neonatal rat model of NEC, and the mechanism underlying this effect was determined. Tat (48-60) YVEEL significantly inhibited TLR4-mediated expression of pro-inflammatory cytokines, p65 nuclear translocation and restored the impaired enterocyte migration in cultured enterocytes. In addition, Tat (48-60) YVEEL administration strikingly increased the survival rate, and reduced the severity of NEC in rats through inhibition of TLR4-mediated signaling. These protective effects of Tat (48-60) YVEEL occurred in a PI3K/AKT dependent manner, as administration of PI3K activator Ys49 abrogated its protective effects. Combined with liposomes, Tat (48-60) YVEEL demonstrated longer retention in the intestines that better for potential clinical applications. These data demonstrate that Tat (48-60) YVEEL protects against NEC through inhibition of TLR4-mediated signaling in a PI3K/AKT dependent manner, and offer a potential therapeutic approach to this disease.